Influence of SiO2 layer on the dielectric function of gold nanoparticles on Si substrate - Chen, T. P. (2014)
The dielectric functions of gold nanoparticle (Au NP) self-assembled on Si substrates without and with a SiO2 layer (3, 10 and 30 nm in thickness) have been examined. For Au NP on Si substrate without a SiO2 layer, a splitting in surface plasmon resonance (SPR) band in the imaginary part of the dielectric function ɛ2 is observed, i.e., besides the typical SPR peak at ∼2 eV, a pronounced peak at ∼1 eV emerges, which is due to the hot spot, that is, a narrow gap between the Au NP and the mirror image. The splitting in the SPR band is greatly suppressed for the 3 nm SiO2 layer and disappears for the 10 nm and 30 nm SiO2 layers, showing that the resonant intensity from the hot spot rapidly attenuates with the gap distance. In addition, the SiO2 layer also has significant influence on the interband transitions of Au NP. These observations are discussed in terms of the image charge effect and the formation of the percolated conductive Au layer on the SiO2 layer.